Study the anticancer mechanism of the promissing compound 2B2D by using microarray technique - Do, Thao Thi; Do, Phuong Thi; Nguyen, Trang Thi; Nguyen, Nga Thi; Huang, Ying Chi (Vietnam Journal of Science and Technology, 2017)
Being a modern technique with the ability of studying, discovering, probing and analyzing the expression of thousands genes, even the whole genome in the only one experiment, microarray proved to be a powerful tool for cancer research especially at molecular level. Employing the potential anticancer compound 1-(5,7-dimetoxy-2,2-dimetyl-2H-cromen-8-yl)-but-2-en-1-on (2B2D in short) and LU-1, the human lung cancer cells as research objects, we successfully hybridized the cy3/5 incorporated cDNA with Phalanx HOV5 microarray. The results showed 742 genes that got effected with equal or over two folds change under 2B2D treatment. Among - those, 386 genes were up-regulated while the other 356 were down-regulated. The Nuclear factor (erythroid-derived 2, regulatory factor X domain containing 1, fibroblast growth factor receptor 3 (achondroplasia, thanatophoric dwarfism) and E2F transcription factor 8 genes were the most stimulated by our compound. The genes that named as Solute carrier family 7 (cationic amino acid transporter, system) member 11, kelch-like 24 and Hypothetical LOC344887 were the most down in action.